Analyzing risk factors for recurrence of developmental coxa vara after surgery. (1st August 2019) - Bian, Z.; Xu, Y. J.; Guo, Y.; Fu, G.; Lyu, X. M.; Wang, Q. Q.
Abstract : Purpose: To evaluate the risk factors for developmental coxa vara (DCV) recurrence following valgus osteotomy of the proximal femur. Methods: We retrospectively reviewed records of 32 DCV patients (46 hips) treated surgically (2005 to 2012). Recurrence-related factors, including age at initial surgery, side, sex, fixation methods, diagnosis of coxa vara, premature capital femoral physeal closure and postoperative Hilgenreiner epiphyseal (HE) angle, head-shaft (HS) angle, medial femoral offset and posterior slope angle (PSA) were analyzed. Results: At 4.7-year mean follow-up, 12 hip deformities recurred (26%). Postoperative HE angle > 41° and negative offset were statistically significant univariate and multivariate risk factors for the deformity recurrence. Increased PSA was common preoperatively, which accounted for 59% of hips. Postoperative PSA > 20° was associated with a high recurrence rate in the univariate analysis. Age was another univariate risk factor for the recurrence. Recurrence rate was 52% in the < 6.5-year age group versus 4% in the > 6.5-year age group. Other factors were not statistically significantly related to recurrence. Conclusion: DCV is a 3D deformity. To prevent recurrence, HE angle should be restored to < 41° in the coronal plane. Sagittal malalignment (abnormal PSA) should be corrected concurrently, so that, the direction of surgical correction is along the true deformity plane. During valgus osteotomy, the distal fragment should be lateralized to maintain a normal mechanical axis. Level of Evidence: IV